Upaya Pelestarian Tradhisi Ruwah Dusun Pacet Made Desa Pacet Kecamatan Pacet Kabupaten Mojokerto - Rizka Alfianita; Sukarman Sukarman (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study aims to explore the efforts of the Pacet Made community in preserving the